Payback's a witch - Harper, Lana (Jove, 2021)
"The witch is back and ready for revenge with a little help from her friends in this fresh, sizzling rom-com by Lana Harper. Emmy Harlow is a witch but not a very powerful one-in part because she hasn't been home to the magical town of Thistle Grove in years. Her self-imposed exile has a lot to do with a complicated family history and a desire to forge her own way in the world, and only the very tiniest bit to do with Gareth Blackmoor, heir to the most powerful magical family in town and casual breaker of hearts and destroyer of dreams. But when a spellcasting tournament that her family serves as arbiters for approaches, it turns out the pull of tradition (or the truly impressive parental guilt trip that comes with it) is strong enough to bring Emmy back. She's determined to do her familial duty; spend some quality time with her best friend, Linden Thorn; and get back to her real life in Chicago. On her first night home, Emmy runs into Talia Avramov-an all-around badass adept in the darker magical arts-who is fresh off a bad breakup...with Gareth Blackmoor. Talia had let herself be charmed, only to discover that Gareth was also seeing Linden-unbeknownst to either of them. And now she and Linden want revenge. Only one question stands: Is Emmy in? But most concerning of all: Why can't she stop thinking about the terrifyingly competent, devastatingly gorgeous, wickedly charming Talia Avramov?"--